Extracellular Vesicles in the Adaptive Process of Prostate Cancer during Inhibition of Androgen Receptor Signaling by Enzalutamide. Issue 23 (20th December 2017) - Soekmadji, Carolina; Rockstroh, Anja; Ramm, Grant A.; Nelson, Colleen C.; Russell, Pamela J.
Abstract: Current treatments for advanced prostate cancer focus on inhibition of the androgen receptor (AR) by androgen deprivation therapy (ADT). However, complex interactions mediated by tumor suppressors, oncogenes, aberrations of AR expression, or de novo androgen production have been shown to induce the adaptive response of prostate cancer, leading to the development of castration resistant prostate cancer. In this study, we report the effects of AR antagonist, enzalutamide on the protein contents of extracellular vesicles (EVs). EVs mediate cell‐to‐cell communication and increasing evidence shows the role of EVs in promoting cancer survival and metastasis. We found that treatment with enzalutamide alters the secretion of EVs, one of which is a plasma membrane calcium pump, ATP2B1/PMCA ATPase, as an AR‐regulated EV protein. We highlight the networks of interactions between AR, Ca 2+, and ATP2B1, where the extracellular proteins thrombospondin‐1, gelsolin, and integrinß1 were previously reported as regulators for cancer progression and metastasis, indicating the potential role of EV‐derived proteins in mediating calcium homoeostasis under AR inhibition by enzalutamide. Our data further highlight the cross‐talk between AR signaling and EV pathways in mediating resistance toward ADT.